Pelatihan Keterampilan Dari Limbah Kemasan Air Mineral di Desa Sambongsari,Weleri Kabupaten Kendal - Fatarina Purwaningtyas, Ery; Mega Kasmiyatun; Ahmad Shobib; Sri Mulyaningsih, MF (Perigel: Jurnal Penyuluhan Masyarakat Indonesia, 2024)
Mineral water packaging waste which is not managed properly, causing environmental pollution. The focus of this service is to provide skills training to the community to process this waste into economically valuable products. The aim of this activity is to increase community awareness and skills in recycling mineral water packaging waste into handicraft items, to reduce environmental pollution and increase community income. Using a participatory approach, with direct training methods involving demonstrations and practice. The strategies used are: 1) Socialization regarding the impact of plastic waste, 2) Technical training on making craft products from mineral water packaging waste. The results of this activity are expected to make people more aware of the importance of managing plastic waste and have new skills in making craft products. The result is products such as bags, wallets and home decorations made from mineral water packaging waste, which can be sold to increase income. Apart from that, there is a reduction in plastic waste in the surrounding environment.